Demand Analysis of English Language Service Value Based on Data Mining Ecosystem - Shao, Chang’en (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Language is a bridge between people, an indispensable component of information exchange and communication, and an essential part of social culture. As the most widely used language in the world, English occupies an essential position in the social language, generating value demands related to it, ranging from the needs of individuals for their development to the needs of social industries or fields for their development to the national language strategy. OBJECTIVES: The purpose of this paper is that due to the implementation of the "One Belt, One Road" policy, more and more cultures of the countries along the route are coming into China’s vision, and at the same time, Chinese culture should also be promoted, and only through the correct use of language can we promote the Chinese civilization and other civilizations to seek common ground and put aside their differences, appreciate each other, and eliminate the clash of cultures in the process of mutual collision and fusion of different civilizations. METHODS: Based on the data mining ecosystem, this study examines the demand analysis of the value of English language services in today’s environment, explores the explicit and implicit benefits regarding the value of English language services, and analyzes and explores the explicit and implicit economic benefits of language services and the economic, social, and cultural benefits they encompass at different levels. RESULTS: The research suggests that we need to focus on the value of multiform English language services, strengthen English language industry research and studies, and conduct a scientific English language economic program. CONCLUSION: Language services and language economy are two closely related concepts. Analyzing language services from multiple perspectives can reveal their explicit and implicit economic, social and cultural benefits.